Functional dimorphism and characteristics of maximal hand grip force in top level female athletes - Ivanovic, J.; Dopsaj, M. (Collegium Antropologicum, 2012)
The aim of this work is to determine functional dimorphism (FmaxNd/DoHGiso) and model characteristics at maximal isometric hand grip force (FmaxHGiso) in top level female athletes. 275 top level female athletes were tested from Taekwondo, Synchronised Swimming, Track and field, Table tennis, Volleyball, Karate, Skiing, Handball, well-trained students (students of the Academy for Criminalistic and Police studies - ACPS) and Control group. In order to assess the FmaxHGiso, we used standardised equipment, i.e., a sliding device that measures isometric finger flexor force, with a tensiometric probe fixed inside the device. The average values of FmaxHGiso and relative force measured by allometric and classic method for dominant and non-dominant hand grip for the total sample were 381.87±60.28, 344.63±55.60 N; 24.06±3.50, 21.72±3.28 N/BM0.667; 0.62±0.10, 0.56±0.09 N/BM. The average value of FmaxNd/DoHGiso was 0.9030±0.0797. General Significant difference was established between subsamples for the measurement characteristics at the level of Wilks' Lambda 0.476, F=3.276, p=0.000. Maximal average value FmaxHGiso for non-dominant and dominant hand is found in Karate (372.04 ±46.71, 407.04±71.31 N) and minimal in Table tennis (282.00±56.00, 304.00±58.51 N). The minimal index value of FmaxNd/DoHGiso was found in Control group 0.8771±0.0877. Considering defined classification of FmaxNd/DoHGiso, we classified the examinees from different sports in 4 groups: dominant symmetry of functional hand grip relations (Skiing> 0.9595); symmetry (Table tennis and Taekwondo 0.9288 to 0.9594); average (Karate, Volleyball, ACPS, Track and field 0.8980 to 0.9287); asymmetry (Control, Synchronised swimming and Handball 0.8674 to 0.8979). The results obtained can be used to determine criteria decisions from the aspect of diagnostic procedures, metric aspect, medical aspect.